Bank stability measures for dual banking system - Abdul Karim, Norzitah; Syed Jaafar Alhabshi, Syed Musa (American Scientific Publishers, 2017)
Bank stability is of paramount importance in the growth of the economy, sustainability and going concern of the financial sector. Thus, it places high reliance on the measures to indicate the stability of the financial institution. There are many indicators used as measures for bank stability. However, the recent Global Financial Crisis showed that despite reports of ‘healthy’ financial institution prior to crisis, these institutions suffered many problems including liquidity, during the crisis. Thus, this led to confusion on reliance of important components of a healthy financial institutions as indicators, leading to loss of confidence on the overall stability of the financial system. Therefore, there is an urgent need for review of the current measures of bank stability that look at the indicators used as measures of banking stability across different jurisdictions. This study aims to develop bank stability index as a measure of bank stability in countries with dual banking system. This methodology rely on qualitative review of literatures and report produced by central banks of different jurisdictions. © 2017 American Scientific Publishers All rights reserved.